5.4.2 Problems 101 to 200

Table 5.417: Second ODE homogeneous ODE

#

ODE

Mathematica

Maple

815

\[ {}y^{\prime \prime }+2 y^{\prime }+y = 0 \]

816

\[ {}y^{\prime \prime }-10 y^{\prime }+25 y = 0 \]

817

\[ {}y^{\prime \prime }-2 y^{\prime }+2 y = 0 \]

818

\[ {}y^{\prime \prime }+6 y^{\prime }+13 y = 0 \]

819

\[ {}x^{2} y^{\prime \prime }-2 x y^{\prime }+2 y = 0 \]

820

\[ {}x^{2} y^{\prime \prime }+2 x y^{\prime }-6 y = 0 \]

821

\[ {}x^{2} y^{\prime \prime }-x y^{\prime }+y = 0 \]

822

\[ {}x^{2} y^{\prime \prime }+x y^{\prime }+y = 0 \]

823

\[ {}y^{\prime \prime }-3 y^{\prime }+2 y = 0 \]

824

\[ {}y^{\prime \prime }+2 y^{\prime }-15 y = 0 \]

825

\[ {}y^{\prime \prime }+5 y^{\prime } = 0 \]

826

\[ {}2 y^{\prime \prime }+3 y^{\prime } = 0 \]

827

\[ {}2 y^{\prime \prime }-y^{\prime }-y = 0 \]

828

\[ {}4 y^{\prime \prime }+8 y^{\prime }+3 y = 0 \]

829

\[ {}4 y^{\prime \prime }+4 y^{\prime }+y = 0 \]

830

\[ {}9 y^{\prime \prime }-12 y^{\prime }+4 y = 0 \]

831

\[ {}6 y^{\prime \prime }-7 y^{\prime }-20 y = 0 \]

832

\[ {}35 y^{\prime \prime }-y^{\prime }-12 y = 0 \]

833

\[ {}x^{2} y^{\prime \prime }+x y^{\prime }-y = 0 \]

834

\[ {}x^{2} y^{\prime \prime }+2 x y^{\prime }-12 y = 0 \]

835

\[ {}4 x^{2} y^{\prime \prime }+8 x y^{\prime }-3 y = 0 \]

836

\[ {}x^{2} y^{\prime \prime }+x y^{\prime } = 0 \]

837

\[ {}x^{2} y^{\prime \prime }-3 x y^{\prime }+4 y = 0 \]

845

\[ {}y^{\prime \prime }-4 y = 0 \]

846

\[ {}2 y^{\prime \prime }-3 y^{\prime } = 0 \]

847

\[ {}y^{\prime \prime }+3 y^{\prime }-10 y = 0 \]

848

\[ {}2 y^{\prime \prime }-7 y^{\prime }+3 y = 0 \]

849

\[ {}y^{\prime \prime }+6 y^{\prime }+9 y = 0 \]

850

\[ {}y^{\prime \prime }+5 y^{\prime }+5 y = 0 \]

851

\[ {}4 y^{\prime \prime }-12 y^{\prime }+9 y = 0 \]

852

\[ {}y^{\prime \prime }-6 y^{\prime }+13 y = 0 \]

853

\[ {}y^{\prime \prime }+8 y^{\prime }+25 y = 0 \]

854

\[ {}y^{\prime \prime }-4 y^{\prime }+3 y = 0 \]

855

\[ {}9 y^{\prime \prime }+6 y^{\prime }+4 y = 0 \]

856

\[ {}y^{\prime \prime }-6 y^{\prime }+25 y = 0 \]

857

\[ {}y^{\prime \prime }-2 i y^{\prime }+3 y = 0 \]

858

\[ {}y^{\prime \prime }-i y^{\prime }+6 y = 0 \]

859

\[ {}y^{\prime \prime } = \left (-2+2 i \sqrt {3}\right ) y \]

860

\[ {}x^{2} y^{\prime \prime }+x y^{\prime }+9 y = 0 \]

861

\[ {}x^{2} y^{\prime \prime }+7 x y^{\prime }+25 y = 0 \]

862

\[ {}\frac {x^{\prime \prime }}{2}+3 x^{\prime }+4 x = 0 \]

863

\[ {}3 x^{\prime \prime }+30 x^{\prime }+63 x = 0 \]

864

\[ {}x^{\prime \prime }+8 x^{\prime }+16 x = 0 \]

865

\[ {}2 x^{\prime \prime }+12 x^{\prime }+50 x = 0 \]

866

\[ {}4 x^{\prime \prime }+20 x^{\prime }+169 x = 0 \]

867

\[ {}2 x^{\prime \prime }+16 x^{\prime }+40 x = 0 \]

868

\[ {}x^{\prime \prime }+10 x^{\prime }+125 x = 0 \]

928

\[ {}x^{2} y^{\prime \prime }+x y^{\prime }-9 y = 0 \]

929

\[ {}4 y^{\prime \prime }-4 y^{\prime }+y = 0 \]

930

\[ {}x^{2} y^{\prime \prime }-x \left (x +2\right ) y^{\prime }+\left (x +2\right ) y = 0 \]

931

\[ {}\left (1+x \right ) y^{\prime \prime }-\left (x +2\right ) y^{\prime }+y = 0 \]

932

\[ {}\left (-x^{2}+1\right ) y^{\prime \prime }+2 x y^{\prime }-2 y = 0 \]

933

\[ {}\left (-x^{2}+1\right ) y^{\prime \prime }-2 x y^{\prime }+2 y = 0 \]

934

\[ {}x^{2} y^{\prime \prime }+x y^{\prime }+\left (x^{2}-\frac {1}{4}\right ) y = 0 \]

1249

\[ {}y^{\prime \prime }+2 y^{\prime }-3 y = 0 \]

1250

\[ {}y^{\prime \prime }+3 y^{\prime }+2 y = 0 \]

1251

\[ {}6 y^{\prime \prime }-y^{\prime }-y = 0 \]

1252

\[ {}2 y^{\prime \prime }-3 y^{\prime }+y = 0 \]

1253

\[ {}y^{\prime \prime }+5 y^{\prime } = 0 \]

1254

\[ {}4 y^{\prime \prime }-9 y = 0 \]

1255

\[ {}y^{\prime \prime }-9 y^{\prime }+9 y = 0 \]

1256

\[ {}y^{\prime \prime }-2 y^{\prime }-2 y = 0 \]

1257

\[ {}y^{\prime \prime }+y^{\prime }-2 y = 0 \]

1258

\[ {}y^{\prime \prime }+4 y^{\prime }+3 y = 0 \]

1259

\[ {}6 y^{\prime \prime }-5 y^{\prime }+y = 0 \]

1260

\[ {}y^{\prime \prime }+3 y^{\prime } = 0 \]

1261

\[ {}y^{\prime \prime }+5 y^{\prime }+3 y = 0 \]

1262

\[ {}2 y^{\prime \prime }+y^{\prime }-4 y = 0 \]

1263

\[ {}y^{\prime \prime }+8 y^{\prime }-9 y = 0 \]

1264

\[ {}4 y^{\prime \prime }-y = 0 \]

1265

\[ {}y^{\prime \prime }-y = 0 \]

1266

\[ {}2 y^{\prime \prime }-3 y^{\prime }+y = 0 \]

1267

\[ {}y^{\prime \prime }-y^{\prime }-2 y = 0 \]

1268

\[ {}4 y^{\prime \prime }-y = 0 \]

1269

\[ {}y^{\prime \prime }-\left (2 \alpha -1\right ) y^{\prime }+\alpha \left (\alpha -1\right ) y = 0 \]

1270

\[ {}y^{\prime \prime }+\left (3-\alpha \right ) y^{\prime }-2 \left (\alpha -1\right ) y = 0 \]

1271

\[ {}2 y^{\prime \prime }+3 y^{\prime }-2 y = 0 \]

1272

\[ {}y^{\prime \prime }+5 y^{\prime }+6 y = 0 \]

1273

\[ {}y^{\prime \prime }-2 y^{\prime }+2 y = 0 \]

1274

\[ {}y^{\prime \prime }-2 y^{\prime }+6 y = 0 \]

1275

\[ {}y^{\prime \prime }+2 y^{\prime }-8 y = 0 \]

1276

\[ {}y^{\prime \prime }+2 y^{\prime }+2 y = 0 \]

1277

\[ {}y^{\prime \prime }+6 y^{\prime }+13 y = 0 \]

1278

\[ {}4 y^{\prime \prime }+9 y = 0 \]

1279

\[ {}y^{\prime \prime }+2 y^{\prime }+\frac {5 y}{4} = 0 \]

1280

\[ {}9 y^{\prime \prime }+9 y^{\prime }-4 y = 0 \]

1281

\[ {}y^{\prime \prime }+y^{\prime }+\frac {5 y}{4} = 0 \]

1282

\[ {}y^{\prime \prime }+4 y^{\prime }+\frac {25 y}{4} = 0 \]

1283

\[ {}y^{\prime \prime }+4 y = 0 \]

1284

\[ {}y^{\prime \prime }+4 y^{\prime }+5 y = 0 \]

1285

\[ {}y^{\prime \prime }-2 y^{\prime }+5 y = 0 \]

1286

\[ {}y^{\prime \prime }+y = 0 \]

1287

\[ {}y^{\prime \prime }+y^{\prime }+\frac {5 y}{4} = 0 \]

1288

\[ {}y^{\prime \prime }+2 y^{\prime }+2 y = 0 \]

1289

\[ {}u^{\prime \prime }-u^{\prime }+2 u = 0 \]

1290

\[ {}5 u^{\prime \prime }+2 u^{\prime }+7 u = 0 \]

1291

\[ {}y^{\prime \prime }+2 y^{\prime }+6 y = 0 \]

1292

\[ {}y^{\prime \prime }+2 a y^{\prime }+\left (a^{2}+1\right ) y = 0 \]

1293

\[ {}t^{2} y^{\prime \prime }+t y^{\prime }+y = 0 \]

1294

\[ {}t^{2} y^{\prime \prime }+4 t y^{\prime }+2 y = 0 \]